Between Clientelism and Strengthening Family Ties: Compadrazgo in the Indigenous Families of the Melipilla Valley (Chile, 1780-1810) [Entre el Clientelismo y el Reforzamiento de Vínculos Familiares: El Compadrazgo en Las Familias Indígenas del Valle de Melipilla (Chile, 1780-1810)] - Armijo-Reyes, A (Instituto Colombiano de Antropologia e Historia, 2020)
This paper analyzes the relations by compadrazgo of the indigenous population of the indigenous people, with the purpose of promoting family strategies aimed at forming clientelism, social mobility and reciprocity alliances between parents and godparents from consanguineal, collateral and family ties, community as well as with the local elite of the Melipilla Valley. The documentation analyzed comes from the parish registry of the San José de Melipilla church, notarial documentation and judicial records, using those through the methodology of social networks to analyze interpersonal links between different sectors and social groups. The results indicate that the links by indigenous compadrazgo between social peers and local elites lead to the search for economic favors as well as social reaffirmation. © 2020 Instituto Colombiano de Antropologia e Historia. All rights reserved.